Nucleolar organizer regions, 18S and 5S rDNA clusters in the chromosomes of Piabina argentea (Characiformes: Characidae) - Piscor, Diovani [UNESP]; Fernandes, Carlos Alexandre; Parise-Maltempi, Patricia Pasquali [UNESP] (Walter De Gruyter Gmbh, 2017)
The Piabina genus was allocated in Stervadiinae subfamily after staying for years as an uncertain group in Characidae. Few cytogenetic studies are described in the literature for Piabina argentea, thus new analyzes in other populations are important to understanding of the chromosomal dynamics of them. The aim of this paper was to analyze the chromosomes of P. argentea from Corumbatai River basin focusing mainly the chromosomal locations of 18S rDNA and 5S rDNA clusters. The diploid chromosome number was 2n = 52 for P. argentea, which were classified as 6 metacentrics (m), 8 submetacentrics (sm), 24 subtelocentrics (st) and 14 acrocentrics (a), and FN (fundamental number) value 90 in both sexes. Silver nitrate impregnation located the nucleolus organizer regions (Ag-NORs) on the short (p) arm of pair 16, however, an intra-individual variation of Ag-NORs sites was observed in two individuals. Fluorescence in situ hybridization (FISH) revealed six 18S rDNA sites (pairs 8, 10 and 16) and four 5S rDNA sites in terminal positions of the short arm of pairs 5 and 22 (one submetacentric and one acrocentric) in P. argentea. The results indicate that, despite the conserved diploid number, this group of fish presents a wide variability of the 18S and 5S rDNA sites.
Keywords: repetitive DNA; FISH; chromosome evolution; Neotropical fish